Design and 3D Printing of Down-scaled Passenger Vehicle Chassis - Öhammar, Anton; Grundén, Jacob; Jaleby, Jon; Arvidsson, Kristofer; Hellsten, Oskar; Medbo, Simon (My University, 2017)
To close the gap between the automotive industry and newly graduated engineers the graduates need to have a better understanding for how their design affects the end result. This thesis focuses on producing 3D printed suspension scale models with correct kinematics to help students better understand how different types of suspensions behave. The suspension types chosen for the models are MacPherson and double wishbone for the front suspensions and trailing arm multi link suspension and a live axle for the rear. These models were designed in Catia V5 and then 3D printed in a scale of 1:5 and assembled together with some off-the-shelf components such as coilover dampers and ball joints. The models for the MacPherson and the trailing arm are based on Chalmers suspension setups while the live axle is based on modified values of the trailing arm. The double wishbone however is primarily based on given requirements and guidelines from the Chalmers suspension setup. The two front suspensions feature functioning steering and the MacPherson one also has a differential to illustrate the function of having a propulsion system. These suspensions are mounted on two vehicle chassis where the front suspensions can be swapped so all the combinations can be shown. The curves for camber gain and bump steer are plotted for the MacPherson and double wishbone suspensions. The 3D printed models have similar kinematics to the original models. Because of the limited accuracy of 3D printing there is some play in the suspension components reducing the similarity between the curves and the real behavior when manipulating the suspensions by hand.
Keywords: Transport; Farkostteknik; Transport; Vehicle Engineering